Economic reform and the political economy of the German welfare state - Wolfgang Streeck; Christine Trampusch (Max Planck Institute for the Study of Societies, 2005)
The key to economic reform in Germany is a significant reduction in the high costs of labour.The main factor driving up German labour costs is the funding of the extensive German welfare state through social insurance contributions that in effect operate like payroll taxes on employment. The paper discusses the political causes of the rise in non-wage labour costs since the 1970s. It then proceeds to show how a variety of opportunities for political blockade in the German political economy dim the prospect for effective reform in the foreseeable future. – – Die Wiederherstellung der Leistungsfähigkeit der deutschen Volkswirtschaft erfordert vor allem eine Reduzierung der hohen Arbeitskosten. Diese werden zu einem erheblichen Teil durch die Beitragsfinanzierung des Sozialstaats verursacht. Die Sozialbeiträge wirken wie Steuern auf Beschäftigung. Das Papier untersucht, warum die Lohnnebenkosten seit den siebziger Jahren so stark gestiegen sind, und zeigt, wie eine Vielfalt von politischen Blockademöglichkeiten effektive Reformen auf absehbare Zeit unwahrscheinlich macht.
Keywords: 300